Bibliometric Analysis of Determinants of Stock Price Returns in Indonesia - Elwisam, Elwisam; Digdowiseiso, Kumba (Atestasi : Jurnal Ilmiah Akuntansi, 2023)
Investment is activity aimed at making a profit. One manifestation of strategic investment management is through selecting the right investment instruments. Currently the instrument with the highest interest in Indonesia is stock. One indicator to measure investment success is stock price returns. Therefore, a study is needed to examine the determinants of stock price returns in Indonesia, so this research is to explain the literature statistics on the determinants of stock stock returns, explain the determinants of stock price returns through bibliometric clustering and density analysis in Indonesia. The data needed is in the form of scientific literature originating from Google Scholar. The results of the research show that (1) the total number of papers that examine the determinants of stock returns in Indonesia is 59 and there has been an increase in studies in the period 2021 to 2023. (2) there are five main topic clusters that are discussed in research, (3) The density model show that there are 19 keywords that appear most frequently, as for these determinants such as deposit interest, exchange rate, profit per share, company financial condition, structure capital, profitability, solvency, price earning ratio, and price to book value.